Analysis and improvement of water use efficiency for crops cultivated in the Mediterranean regions: the state of the art - Katerji N.; Mastrorilli M.; Rana G. (WEMED workshop: how to advance the knowledge on water use efficiency in the Mediterranean region ?, 2007)
The improvement of water use efficiency (WUE) of field crops in the Mediterranean region is an imperative imposed by the critical situation of water resources of the region, as well as by the demographical increment. This review reports the experimental data concerning the WUE of 15 species cultivated in the region, including cereals, leguminous, horticultural and industrial crops. This review however underlines that WUE data of fruit trees are lacking, despite they represent one of the main productions of the Mediterranean agriculture. The variability of WUE can be ascribed mainly to: (i) mineral and water management (water regime, mineral supply and water quality); (ii) plant factors (growth stage sensitivity and varietal response to the stress); and (iii) environmental factors (climate, atmospheric pollution, soil texture and climate change). The conclusion highlights the actual gap concerning water use efficiency in the Mediterranean region. This gap will constitute a field of research designated to ameliorate water use efficiency of agriculture in this region.
Workshop on: How to Advance the Knowledge on Water Use Efficiency in the Mediterranean Region ? 2006/10/26-28, Valenzano (Italy)